Empowering teachers : what successful principals do - Blase, Joseph; Blase, Jo Roberts (Thousand Oaks, Calif. : Corwin Press, 2001)
Updated Edition of Best Seller!Based on interviews with over 800 teachers, the authors show the transformative effects principals can have on teachers' work both in the classroom and in the wider school setting.
Includes bibliographical references.
Keywords: Teacher participation in administration -- United States; School principals; Teacher-principal relationships -- United States